TOOLS OF ACTIVE INVOLVEMENT OF FUTURE SOCIAL WORKERS IN INNOVATIVE ACTIVITY - Savelchuk, Iryna Borysivna (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2021)
The article considers the problem of involving students in innovative activities by means of educational technologies of professional training. The issue of resource provision, which will contribute to the creation of an innovative educational environment for professional training, remains a priority. Emphasis is placed on the need to use innovative, interactive technologies to train future social workers. The tools that can ensure the active involvement of students in innovative activities are identified.